The Association Between Cadmium Exposure and Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Lin, Yu; Li, Ting; Xiao, Jiangbo; Xie, Kaipeng; Shi, Zhonghua (Frontiers in Public Health, 2022)
Objective: Several studies have evaluated the association of cadmium exposure with the risk of gestational diabetes mellitus (GDM). However, the findings among these studies have been inconsistent. To further investigate the relationship, we carried out a meta-analysis to clarify the relationship between cadmium exposure and GDM risk. Methods: Five databases (Scopus, PubMed, Web of Science, Cochrane and CNKI) were searched for eligible studies until September 09, 2021. The quality of eligible studies was evaluated using the Newcastle-Ottawa quality assessment scale (NOS). The summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated by random effects models due to high heterogeneity. Sensitivity analysis was performed to explore the robustness of the results. Publication bias was evaluated by Egger’s test and Begg’s test. We also conducted meta-regression analysis and subgroup analysis to assess the potential sources of heterogeneity. Results: A total of 10 studies with 32,000 participants related to our issue were included. Comparing the highest versus lowest categories of cadmium exposure, no significant association was observed between cadmium exposure and the risk of GDM (OR=1.16, 95% CI=0.92-1.46, P =0.206). No publication bias was found in Begg’s and Egger’s tests (all P >0.05). Meta-regression suggested that publication year was the potentially heterogeneous source (P = 0.034). Subgroup analysis of publication year showed that studies before the year of 2016 was 4.05 (95% CI=1.87-8.76, P <0.001), and prospective cohort studies showed a borderline increased GDM risk (OR=1.15, 95% CI=0.99-1.33, P =0.061). Conclusion: Our results indicated no significant association between cadmium exposure and GDM risk. Further high-quality prospective studies, especially standard analytic method for cadmium exposure, are warranted to confirm the results.